Honokiol attenuates oxidative stress-induced cytotoxicity in human keratinocytes via activating AMPK signaling - Yung Hyun Choi (Asian Pacific Journal of Tropical Biomedicine, 2021)
Objective: To investigate the effect of honokiol on oxidative damage in HaCaT human keratinocytes. Methods: HaCaT cells were exposed to hydrogen peroxide (H2O2), following pretreatment with various concentrations of honokiol. The alleviating effects of honokiol on HaCaT cell viability and cell death, reactive oxygen species (ROS) production, DNA damage, mitochondrial dynamics, and inhibition of adenosine triphoaphate production against H2O2 were investigated. Western blotting analysis was used to analyze the expression levels of specific proteins. Results: Honokiol suppressed H2O2-induced cytotoxicity and DNA damage by blocking abnormal ROS accumulation. Honokiol also prevented apoptosis by inhibiting loss of mitochondrial membrane potential and release of cytochrome c from the mitochondria into the cytosol, decreasing the Bax/Bcl-2 ratio, and reducing the activity of caspase-3 in H2O2-stimulated HaCaT cells. In addition, honokiol attenuated H2O2-induced reduction of adenosine triphosphate content, and activation of AMP-activated protein kinase (AMPK) was markedly promoted by honokiol in H2O2-stimulated cells. Importantly, the anti-apoptosis and anti-proliferative activity of honokiol against H2O2 was further enhanced by adding an activator of AMPK, indicating that honokiol activated AMPK in HaCaT keratinocytes to protect against oxidative damage. Conclusions: The present results indicate that honokiol may be useful as a potential therapeutic agent against various oxidative stress-related skin diseases.